The relationship between SPELD and schools in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Auckland, New Zealand - Devine, Jennifer Mary (Massey University, 2010)
This research investigated the relationship between SPELD teachers and classroom teachers from the Wellington region. A key issue identified in a 2009/2010 evaluation of the SPELD New Zealand organisation was the lack of effective collaboration between SPELD teachers and individuals in the education sector. The present study sought to identify what supports SPELD and schools to work together, what factors restrict the relationship between SPELD and schools, and how can collaboration between SPELD and schools be enhanced. Using a case study methodology, this research investigated SPELD teachers’ views and experiences about their relationships with classroom teachers and the schools in which they operate and classroom teachers’ views and experiences about their relationships with SPELD teachers and the SPELD organisation in which they operate. The study found that while there were a number of positive factors contributing to an effective collaborative relationship between SPELD teachers and school teachers, there were a number of issues restricting the relationship. In particular, issues arose concerning tutoring within school hours and alignment with the work and schedules of existing specialist staff. Suggestions are offered about ways in which collaboration between SPELD and schools could be enhanced.
Keywords: NZ Federation of Specific Learning Disabilities; Dyslexic children; Education; Remedial reading; Schools; Cooperation; New Zealand; Dyslexics; Co-operation